Geochemical signature of rift relocations at Iceland - Walters, Rachel Lucy (Trinity College (Dublin, Ireland). Department of Geology, 2010)
Iceland is located at the intersection between the Mid-Atlantic Ridge and a mantle plume. Three active rift segments at Iceland represent the onshore expression of the Mid-Atlantic Ridge. Iceland’s tectonic evolution has been dominated by rift relocations, a process where extension across one rift segment is gradually transferred to a new adjacent rift segment. Rift relocations are driven by the northwestward migration of Iceland over the mantle plume conduit, which is currently located underneath Vatnajokull icecap in central Iceland. The complete rift cycle is represented by the currently active Eastern Volcanic Zone (birth). Northern Volcanic Zone (steady-state) and Western Volcanic Zone (decline). The aim of this dissertation is to characterise the geochemical signature of the different rift stages at Iceland and link differences in the lava chemistry with variations in the mantle melt compositions and melting process. Rift relocations result in significant changes in the spreading rate because two adjacent rifts axe simultaneously active for several million years. In the first part of the dissertation, the geochemical signatures of all the active volcanic zones at Iceland, lavas from near the most recently extinct spreading axis, lavas from off-axis volcanic centres and Tertiary lavas are charaterised and compared to each other. In the second part, a new time-dependent model of upwelling and melting beneath a mid-ocean ridge is developed to understand the effects of spreading rate variations on the depth and degree of melting, and the resultant melt composition.
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin